2009
DOI: 10.1007/s00415-009-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of neuromyelitis optica in Cuba

Abstract: This Cuban multiethnic population had a prevalence of NMO of 0.52 per 100,000 and an estimated average annual incidence rate of 0.053 per 100,000 with no differences by ethnicity. Black patients were older, with more relapses and motor impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(147 citation statements)
references
References 39 publications
5
134
1
6
Order By: Relevance
“…The hamstring and gluteal muscle weakness can lead to lower interstitial and imbalance syndrome; this imbalance can have harmful effects on the static and dynamic status of the body, especially when walking. This syndrome increases the anterior pelvic tilt and in the spine increases lumbar lordosis and a small hip flexion (1,11) It is reported that that MS patients suffer from postural and physical impairment, they cannot directly maintain their postures, which, as a result of this defect, disabilities are increased in posture and spinal column (9). There are little research on spinal cord abnormalities in MS patients and healthy partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hamstring and gluteal muscle weakness can lead to lower interstitial and imbalance syndrome; this imbalance can have harmful effects on the static and dynamic status of the body, especially when walking. This syndrome increases the anterior pelvic tilt and in the spine increases lumbar lordosis and a small hip flexion (1,11) It is reported that that MS patients suffer from postural and physical impairment, they cannot directly maintain their postures, which, as a result of this defect, disabilities are increased in posture and spinal column (9). There are little research on spinal cord abnormalities in MS patients and healthy partners.…”
Section: Discussionmentioning
confidence: 99%
“…Today, in terms of epidemiology, noncommunicable diseases are responsible for 60% of the world's death and mortality cases (1). Among these diseases, diabetes, asthma, multiple sclerosis etc.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] NMO is a B-cell-mediated inflammatory and demyelinating disorder of the central nervous system, often presenting with severe and bilateral recurrent optic neuritis and transverse myelitis that are radiological distinguished from multiple sclerosis (MS). 5,6 Early detection of NMO is facilitated by the testing for the neuromyelitis optica immunoglobulin G (NMO-IgG) antibody.…”
Section: Case Reportmentioning
confidence: 99%
“…NMO is rare and accounts for only 1% of all demyelinating diseases [26][27][28]. The incidence of NMO is estimated to be approximately 4 per million of the population and the prevalence is somewhere between 3 and 44 per million, depending on ethnicity and geographic location [26][27][28][29].…”
Section: Neuromyelitis Opticamentioning
confidence: 99%
“…NMO is rare and accounts for only 1% of all demyelinating diseases [26][27][28]. The incidence of NMO is estimated to be approximately 4 per million of the population and the prevalence is somewhere between 3 and 44 per million, depending on ethnicity and geographic location [26][27][28][29]. Disease onset is usually in the fourth decade of life; women are affected more commonly than men (approximately 3:1); and non-Caucasians (especially Japanese) are affected more commonly than Caucasians [29][30][31][32].…”
Section: Neuromyelitis Opticamentioning
confidence: 99%